(untitled) (Al-Aasar, 2025)
This analytical study examines the impact of sectarian narratives on the religious identity formation of Muslim youth in contemporary societies.Sectarianism defined social division along with religious, ethical formation and social policy engagement of youth across diverse contexts.Youth in sectarianized communities or Societies frequently experience identity confusion due to competing narrative, lack of communities, as a result their social tolerance, civil participation, and social cohesion are significantly affected. Sectarianism profoundly influenced youth’s identity. Sectarianized societies are a religious framework for moral reasoning, ethical behavior, and community belongings. Youth can also socialize into sectarian identities through familites, educational institutions and religious associations attachment to one’s sect is different from sectarianism which is excessive attachment to a particular group or sect especially based on religion. Sectarianism may be a cause of intolerance and conflicts in groups or sects. This abstract synthesis insights from Qualitative and Quantitate research to Understand youth identity in sectarianized societies .it is essential to examine socio political structures, educational systems and youth agency. This study also emphasized the transformative potential of youth centered interventions that promote tolerance and social cohesion in the context of entrenched Sectarianism. This study contributes to the broader discourse on youth identity, religious socialization, and intra-Muslim harmony, offering recommendations for educators.